2012
DOI: 10.1007/s12668-012-0050-9
|View full text |Cite
|
Sign up to set email alerts
|

Microwell Regulation of Pluripotent Stem Cell Self-Renewal and Differentiation

Abstract: The fates of pluripotent stem cells (PSCs), including survival, self-renewal, and differentiation, are regulated by chemical and mechanical cues presented in the three-dimensional (3D) microenvironment. Most PSC studies have been performed on two-dimensional substrates. However, 3D culture systems have demonstrated the importance of intercellular interactions in regulating PSC self-renewal and differentiation. Microwell culture systems have been developed to generate homogenous PSC colonies of defined sizes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 80 publications
(95 reference statements)
0
14
0
Order By: Relevance
“…The shape of the microwell can be modified into different shapes, including rectangles and triangles (3). Various cell types have been applied to microwells, including embryonic stem cells, islet cells and hepatocytes (5,17,18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The shape of the microwell can be modified into different shapes, including rectangles and triangles (3). Various cell types have been applied to microwells, including embryonic stem cells, islet cells and hepatocytes (5,17,18).…”
Section: Discussionmentioning
confidence: 99%
“…The fates of stem cells, including survival, self-renewal and differentiation, are regulated by chemical and mechanical stimuli presented in their three-dimensional microenvironment (3). The majority of stem cell studies have been performed on two-dimensional substrates (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These various determinants such as growth factors and epigenetic modifiers are constantly connected to stem cells, thus regulating their ability for self-renewal, proliferation, and differentiation. 45,47,150 However, to assess characteristics of a stem cell, we need technical access to different time points of the same stem cell or its lineages.…”
Section: Figmentioning
confidence: 99%
“…To this end, various materials‐based culture platforms have been engineered to systematically study how microenvironmental contributions, such as substrate stiffness, extracellular matrix (ECM) proteins, scaffolding, and mechanical stimuli, affect ESC behavior . 3‐D microwell cell culture platforms have been utilized to modulate cell–cell contact, intercellular, and autoregulatory signaling that occur in hESCs and during differentiation, particularly in embryoid body (EB)‐based differentiation . Some studies have demonstrated that pro‐pluripotency autoregulation can be accentuated in various configurations of 3‐D microwell culture .…”
Section: Introductionmentioning
confidence: 99%